Legal Liability of Electronic Money Corruption as a Crime of Origin of Money Laundering Crime - Arifin Said Ritonga; Triono Eddy; Adi Mansar (Faculty of Law, Universitas Pekalongan, 2025)
Money is a very crucial aspect of human life. Changes in the way we use money are evolving rapidly, along with advances in technology and information. Both notes and coins have transformed into electronic money. The law, specifically Article 17 to Article 22 of the ITE Law, regulates electronic transactions, also known as e-commerce buying and selling contracts. Article 17 paragraph (2) of the ITE Law states that parties conducting electronic transactions as mentioned in paragraph (1) must act in good faith when interacting and/or exchanging electronic documents and electronic information during such transactions. Article 18 paragraph (2) states that the party conducting electronic transactions as mentioned in paragraph (1) This research is a normative legal research, namely a legal study that positions law as a structured system of norms. The type of normative legal research is law that is formulated based on norms or rules that apply in society and become a guideline for the behavior of each individual. Money laundering in general can be defined as an act or actions that transfer, use or perform other actions or the proceeds of a criminal act that is often carried out by crime organizations or individuals who commit acts of corruption, narcotics trafficking, and other criminal acts. The goal is to hide or obscure the origin of the illicit money so that it can be used as if it were legitimate money.